The impact of gut microbiota on autoimmune thyroiditis and relationship with pregnancy outcomes: a review - Song, Yu; Bai, Yu; Liu, Cong; Zhai, Xiaodan; Zhang, Le (Frontiers in Cellular and Infection Microbiology, 2024)
Autoimmune thyroiditis (AITD) is a T-cell-mediated, organ-specific autoimmune disease caused by interactions between genetic and environmental factors. Patients with AITD show thyroid lymphocyte infiltration and an increase in the titer of thyroid autoimmune antibodies, thereby altering the integrity of thyroid follicle epithelial cells and dysregulating their metabolism and immune function, leading to a decrease in multi-tissue metabolic activity. Research has shown that patients with AITD have a significantly higher risk of adverse pregnancy outcomes, such as infertility and miscarriage. Levothyroxine(LT 4 ) treatment can improve the pregnancy outcomes of normal pregnant women with thyroid peroxidase antibodies(TPOAb) positivitye, but it is not effective for invitro fertilization embryo transfer (IVF-ET) in women with normal thyroid function and positive TPOAb. Other factors may also influence pregnancy outcomes of patients with AITD. Recent studies have revealed that the gut microbiota participates in the occurrence and development of AITD by influencing the gut-thyroid axis. The bacterial abundance and diversity of patients with Hashimoto thyroiditis (HT) were significantly reduced, and the relative abundances of Bacteroides, fecal Bacillus, Prevotella, and Lactobacillus also decreased. The confirmation of whether adjusting the composition of the gut microbiota can improve pregnancy outcomes in patients with AITD is still pending. This article reviews the characteristics